Theoretical modeling of the carbon dioxide injection into the porous medium saturated with methane and water taking into account the CO2 hydrate formation - Gubaidullin, A. A.; Musakaev, N. G.; Hai, Duong Ngoc; Borodin, S. L.; Thai, Nguyen Quang; Thang, Nguyen Tat (Vietnam Journal of Mechanics, 2018)
In this work the mathematical model is constructed and the features of the injection of warm carbon dioxide (with the temperature higher than the initial reservoir temperature) into the porous reservoir initially saturated with methane gas and water are investigated. Self-similar solutions of the one-dimensional problem describing the distributions of the main parameters in the reservoir are constructed. The effect of the parameters of the injected carbon dioxide and the reservoir on the intensity of the CO2hydrate formation is analyzed.